Systematic review and meta-analysis of school-based obesity interventions in mainland China. - Lin Feng; Dong-Mei Wei; Shen-Ting Lin; Ralph Maddison; Cliona Ni Mhurchu; Yannan Jiang; Yang Gao; Hai-Jun Wang (PLoS ONE)
Background Numerous school-based interventions for childhood obesity have been emerging in mainland China in recent decades, but little is known about the effectiveness of such interventions. This study aims to assess the effectiveness of school-based interventions for childhood obesity conducted in mainland China. Methods A systematic search was undertaken in eight databases to identify both randomized and non-randomized controlled trials from January 1990 to December 2015 examining the effectiveness of school-based obesity interventions. A random effects meta-analysis was conducted assessing the impact of included interventions on (body mass index) BMI. The quality of each included studies were assessed using Effective Public Health Practice Project Quality Assessment Tool. A P value <0.05 (two-sided) was considered statistically significant. Result Of the seventy-six included studies, we found physical activity and health education were the two most common components of interventions. More treatment studies were effective compared with prevention studies (85.0% vs. 58.3%). Comprehensive interventions involving physical activity and health education appeared more effective than the physical activity only interventions in both obesity treatment and prevention studies. The meta-analyses showed comprehensive interventions involving physical activity and health education had larger effect on the change of BMI than physical activity only interventions (treatment studies: -1.80 kg/m2 (95% CI: -2.15,-1.44) vs. -0.91 kg/m2 (95% CI: -1.15,-0.67); prevention studies: -0.19 kg/m2 (95% CI: -0.27, -0.11) vs. +0.05 kg/m2 (95% CI: -0.04, +0.15)). Conclusions Comprehensive school-based interventions may assist in tackling the rising prevalence of childhood obesity in mainland China.